Revisiting the birth locations of pulsars B1929+10, B2020+28, and B2021+51 - Kirsten, Franz; Vlemmings, W.; Campbell, R.; Kramer, M.; Chatterjee, S. (EDP Sciences, 2015)
We present new proper motion and parallax measurements obtained with the European VLBI Network (EVN) at 5GHz for the three isolated pulsars B1929+10, B2020+28, and B2021+51. For B1929+10 we combined our data with earlier VLBI measurements and confirm the robustness of the astrometric parameters of this pulsar. For pulsars B2020+28 and B2021+51 our observations indicate that both stars are almost a factor of two closer to the solar system than previously thought, placing them at a distance of 1.39-0.06+0.05 and 1.25-0.17+ 0.14kpc. Using our new astrometry, we simulated the orbits of all three pulsars in the Galactic potential with the aim to confirm or reject previously proposed birth locations. Our observations ultimately rule out a claimed binary origin of B1929+10 and the runaway star ζ Ophiuchi in Upper Scorpius. A putative common binary origin of B2020+28 and B2021+51 in the Cygnus Superbubble is also very unlikely.